Electrochemical Determination of Aflatoxin B1 (AFB1) Using a Copper-Based Metal-Organic Framework (Cu-MOF) and Gold Nanoparticles (AuNPs) with Exonuclease III (Exo III) Assisted Recycling by Differential Pulse Voltammetry (DPV). (2nd November 2019) - Wang, Chunyan; Zhang, Hui; Jiang, Xiaoqing; Zhou, Bo
Abstract: A sensitive electrochemical biosensor was designed for determination of aflatoxin B1 (AFB1) using a copper-based metal-organic framework (Cu-MOF), which has strong electrochemical activity and exonuclease III (Exo III)-assisted recycling for dual signal amplification. Hairpin DNA (S1) was immobilized on the electrode. The AFB1 was recognized by aptamer DNA (S2) and complementary DNA (S3) was released. The S3 hybridized with the hairpin S1 to form the Exo III hydrolyzed double-stranded DNA, leaving a partial sequence of hairpin DNA (S1′) on the electrode and releasing S3 for the next cycle of the opening and digestion of hairpin S1. The amplified S1′ then was able to combine with more signal probes. Cu-MOF bond gold nanoparticles (AuNPs) by -NH2 were immobilized to capture DNA (S4) to obtain Cu-MOF/AuNPs/S4. This signal probe Cu-MOF/AuNPs/S4 was able to hybridize with the electrode and generate an amplified electrochemical signal. Under the optimized conditions, this electrochemical biosensor for AFB1 exhibited a low detection limit of 6.7 × 10 −7 ng/mL at a signal-to-noise equal to 3 and a wide linear range from 10 −6 to 1 ng/mL. The biosensor was also used to analyze AFB1-spiked beer sample with recovery values between 96% and 103%. This method has the potential to become a valuable technology for detecting various toxins by the selection of the appropriate aptamer DNA.